MicroRNA-133a engineered mesenchymal stem cells augment cardiac function and cell survival in the infarct heart - Dakhlallah, Duaa (J Cardiovasc Pharmacol, 2015)
Cardiovascular disease is the number one cause of morbidity and mortality in the United States. The most common manifestation of cardiovascular disease is myocardial infarction (MI), which can ultimately lead to congestive heart failure (CHF). Cell therap (cardiomyoplasty) is a new potential therapeutic treatment alternative for the damaged heart. Recent preclinical and clinical studies have shown that mesenchymal stem cells (MSCs) are a promising cell type for cardiomyoplasty applications. However, a major limitation is the poor survival rate of transplanted stem cells in the infarcted heart. miR-133a is an abundantly expressed microRNA in the cardiac muscle and is down-regulated in patients with MI. We hypothesized that reprogramming MSCs using microRNA-mimics (double-stranded oligonucleotides) will improve survival of stem cells in the damaged heart. MSCs were transfected with miR-133a mimic and antagomirs and the levels of miR-133a were measured by qRT-PCR. Rat hearts were subjected to MI and MSCs transfected with miR-133a mimic or antagomir were implanted in the ischemic heart. Four weeks after MI, cardiac function, cardiac fibrosis, miR-133a levels and apoptosis related genes (Apaf-1, Capase-9 and Caspase-3) were measured in the heart. We found that transfecting MSCs with miR-133a mimic improves survival of MSCs as determined by the MTT assay. Similarly, transplantation of miR-133a mimic transfected MSCs in rat hearts subjected to MI led to a significant increase in cell engraftment, cardiac function and decreased fibrosis when compared with MSCs only or MI groups. At the molecular level, qRT-PCR data demonstrated a significant decrease in expression of the pro-apoptotic genes; Apaf-1, caspase-9 and caspase-3 in the miR-133a mimic transplanted group. Further, luciferase reporter assay confirmed that miR- 133a is a direct target for Apaf-1. Overall, bioengineering of stem cells through miRNAs manipulation could potentially improve the therapeutic outcome of patients undergoing stem cell transplantation for myocardial infarction.